Effects of Vitamin A Supplementary in the Feed to Reduce Toxic Effects of Aflatoxin B1 on Japanese Quails (Coturnix coturnix Japonica) - Denli, Muzaffer; Celik, Kemal; Okan, Ferda (International Journal of Poultry Science, 2003)
A study was conducted to determine the efficacy of the antioxidant vitamin A, for reducing aflatoxicosis in Japanese quail (Coturnix coturnix Japonica) from hatch to 35 d of age. Sixty Japanese quail chicks were randomly divided into four groups, three treatments and one control. Control group was fed a basal diet while the treatment diets were supplemented with vitamin A (15,000 IU/kg feed), vitamin A (15,000 IU/kg) + low level of aflatoxin B1 (100 μg/kg) or aflatoxin B1 (100 μg/kg). The liver was swollen and a bright yellow color; microscopically fatty metamorphosis, necrotic areas and infiltration of polymorphonuclears were observed in aflatoxin B1 group and was not seen in any other groups. Compared to control, aflatoxin B1 (AFB1) reduced body weight gain (BWG) and feed conversion rate (FCR) by 9.3 and 7.6 % respectively. The addition of 15,000 IU/kg of vitamin A without aflatoxin B1 improved quail growth performance. Dietary vitamin A had affect on BWG and feed consumption (P<0.05) and reduced the toxic effects of AFB1, addition resulted less toxicity in the liver and kidney than AFB1 group. FC was found significantly important during third and fourth weeks in vitamin A and AFB1 added group (P<0.05) FCR was also better than AFB1 group. The concentration of liver function enzymes serum glutamic pyruvic transaminase (GPT), serum glutamic-oxaloacetic transaminase (GOT), alkaline phosphatase (ALP) increased when AFB1 was added to the diet, whereas the supplementation of the diet Vitamin A partially decreased this negative effects. These results demonstrate that vitamin A plays a complex role in the process of chemical aflatoxicosis and when added at 15.000 IU/kg in the diet can provide protection against the harmful effects of AFB1 for experimental period in Japanese quail.